2009
DOI: 10.1111/j.1467-8535.2008.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

A case study of the development of WebPA: An online peer‐moderated marking tool

Abstract: Peer moderation of group work in higher education is rapidly advancing through the use of technological developments and is increasingly being informed by pedagogical research. The highly successful WebPA online assessment system has gone through a number of development phases over its 15-year history and has now evolved into a relatively mature and flexible tool for facilitating group work. This paper presents a case study of the approaches that have been used in the system's development from the technical pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…However, the majority of these studies also report the variable impact of peer feedback on student performance (Ballantyne et al, 2002;Bloxham & West, 2004). Loddington, Pond, Wilkinson, and Willmot (2009) found that only more mature students appreciated peer assessment as an educational support and teamwork development tool. Gielen et al (2011) noted that performance of students did improve but not for high-ability assessees.…”
Section: Core Themesmentioning
confidence: 99%
“…However, the majority of these studies also report the variable impact of peer feedback on student performance (Ballantyne et al, 2002;Bloxham & West, 2004). Loddington, Pond, Wilkinson, and Willmot (2009) found that only more mature students appreciated peer assessment as an educational support and teamwork development tool. Gielen et al (2011) noted that performance of students did improve but not for high-ability assessees.…”
Section: Core Themesmentioning
confidence: 99%
“…Technological innovations and developments have been used to engage students in the process of peer assessment and peer feedback (Freeman and McKenzie 2002;Li, Liu, and Steckelberg 2010;Loddington et al 2009). Both Freeman and McKenzie (2002) and Loddington et al (2009) illustrate that the use of technology can improve the fairness of group assessment by acknowledging, rating and rewarding individual contributions and enhancing students' learning from team tasks, whereas Li, Liu, and Steckelberg (2010) found a significant relationship between the quality of the peer feedback the students provided for others and the quality of the students' own final projects.…”
Section: Peer Assessmentmentioning
confidence: 99%
“…The SMARTER extends CATME and attempts to link educational research with teaching faculty actions to enhance learning of teamwork skills [19]. Finally, WebPA is an online peermoderated marking system [16]. It is designed for giving individual marks to students working in groups and doing group-work, whose outcome of earns an overall group mark.…”
Section: Computer Assisted Peer Assessmentmentioning
confidence: 99%